Credit Efficiency: Another Indicator for Systemic Risk - Tang, Chenyao (Université d'Ottawa | University of Ottawa, 2024)
Credit booms can lead to differing outcomes. Some credit booms are precursors to financial crises, incurring extremely high costs, while others result from high productivity and act as catalysts for economic growth. Identifying harmful booms and providing early warnings of financial crises as accurately as possible remains a key unresolved issue. Based on the theory that "The crisis is explained by a sudden collapse in the marginal efficiency of capital" (Keynes, 1936) and "The financing structure determines whether the financial system is steady" (Minsky, 1986), this study proposes a new early warning indicator - the credit efficiency indicator. This indicator uses the growth rate of credit efficiency to differentiate types of credit booms and capture early signals of financial crises. Although leverage is often associated with economic vulnerability, the allocation and efficiency of credit output is a less explored indicator. This study analyzed data sets from G20 member countries over the past 30 years and tested the early warning capability of this indicator through fixed effects models, difference models, and crisis prediction models. The verification results show that the credit efficiency indicator has a unique and significant risk prediction ability: a continuous slowdown in the growth rate of credit efficiency significantly increases the probability of a financial crisis, and inefficient credit booms are dangerous. Moreover, this study explored the joint effect of credit efficiency and leverage levels and proposed using credit efficiency as an indicator for structured credit adjustment, providing new perspectives and tools for credit policy formulation and financial regulation.
Keywords: systemic risk; financial crises; credit boom; credit efficiency; early warning indicator